A predictive framework for the reproducible seed-mediated synthesis and functionalization of gold nanorods - Brian Novati; Lucia Salvioni; Melissa Saibene; Alessandro Colombo; Roberto Lorenzi; Angelo Monguzzi; Stefania Garbujo; Miriam Colombo; Marco D. Giustra; Davide Prosperi (Chemical Engineering Journal, 2026)

One-Click CT-Based Pipeline for Regional Quantification of Aortic Valve Fibrocalcific Degeneration - Marta Liberotti; Anna Palmisano; Alberto Colombo; Davide Vignale; Federica Piccione; Marco Bruno Ancona; Matteo Montorfano; Antonio Esposito (Annals of Biomedical Engineering, 2026)

Urban land surface temperature and landscape features shape pathogen occurrence among honey bees and three wild bee species - Beatrice Colombo; Nicola Tommasi; Davide Maggioni; Andrea Galimberti; Giovanni Cilia (Urban Ecosystems, 2026)

Lawn management promoting tall herbs, flowering species and urban park attributes enhance insect biodiversity in urban green areas - Paolo Biella; Sara Borghesan; Beatrice Colombo; Andrea Galimberti; Lorenzo Guzzetti; Davide Maggioni; Emiliano Pioltelli; Fausto Ramazzotti; Rosa Ranalli; Nicola Tommasi; Massimo Labra (Urban Forestry & Urban Greening, 2025)

Experimental study on coalescer efficiency for liquid-liquid separation - Igor Matteo Carraretto; Davide Scapinello; Riccardo Bellini; Riccardo Simonetti; Luca Molinaroli; Luigi Pietro Maria Colombo; Giampaolo Manzolini (Desalination, 2024)

Cardiorespiratory coupling in mechanically ventilated patients studied via synchrogram analysis - Davide Ottolina; Beatrice Cairo; Tommaso Fossali; Claudio Mazzucco; Antonio Castelli; Roberto Rech; Emanuele Catena; Alberto Porta; Riccardo Colombo (Medical & Biological Engineering & Computing, 2023)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

The hidden interplay between sex and COVID-19 mortality: the role of cardiovascular calcification - Alberto Cereda; Marco Toselli; Anna Palmisano; Davide Vignale; Riccardo Leone; Valeria Nicoletti; Chiara Gnasso; Antonio Mangieri; Arif Khokhar; Gianluca Campo; Alessandra Scoccia; Matteo Bertini; et al. (GeroScience, 2021)
Recent clinical and demographical studies on COVID-19 patients have demonstrated that men experience worse outcomes than women. However, in most cases, the data were not stratified according to gender, limiting the understanding of the real impact of gender on outcomes. This study aimed to evaluate the disaggregated in-hospital outcomes and explore the possible interactions between gender and cardiovascular calcifications. Data was derived from the sCORE-COVID-19 registry, an Italian multicentre registry that enrolled COVID-19 patients who had undergone a chest computer tomography scan on admission. A total of 1683 hospitalized patients (mean age 67±14 years) were included. Men had a higher prevalence of cardiovascular comorbidities, a higher pneumonia extension, more coronary calcifications (63% vs.50.9%, p<0.001), and a higher coronary calcium score (391±847 vs. 171±479 mm 3 , p <0.001). Men experienced a significantly higher mortality rate (24.4% vs. 17%, p =0.001), but the death event tended to occur earlier in women (15±7 vs. 8±7 days, p = 0.07). Non-survivors had a higher coronary, thoracic aorta, and aortic valve calcium score. Female sex, a known independent predictor of a favorable outcome in SARS-CoV2 infection, was not protective in women with a coronary calcification volume greater than 100 mm 3 . There were significant differences in cardiovascular comorbidities and vascular calcifications between men and women with SARS-CoV2 pneumonia. The differences in outcomes can be at least partially explained by the different cardiovascular profiles. However, women with poor outcomes had the same coronary calcific burden as men. The presumed favorable female sex bias in COVID-19 must therefore be reviewed in the context of comorbidities, especially cardiovascular ones.

Neutralization of extracellular NAMPT (nicotinamide phosphoribosyltransferase) ameliorates experimental murine colitis - Giorgia Colombo; Nausicaa Clemente; Andrea Zito; Cristiano Bracci; Federico Simone Colombo; Sabina Sangaletti; Elena Jachetti; Davide Giuseppe Ribaldone; Gian Paolo Caviglia; Luca Pastorelli; Marco De Andrea; Samuele Naviglio; et al. (Journal of Molecular Medicine, 2020)

A Glutamate Transporter EAAT1 Gene Variant Influences Amygdala Functional Connectivity in Bipolar Disorder - Sara Poletti; Martina Riberto; Benedetta Vai; Davide Ghiglino; Cristina Lorenzi; Alice Vitali; Silvia Brioschi; Clara Locatelli; Alessandro Serretti; Cristina Colombo; Francesco Benedetti (Journal of Molecular Neuroscience, 2018)

New results on ground deformation in the Upper Silesian Coal Basin (southern Poland) obtained during the DORIS Project (EU-FP 7) - Marek Graniczny; Davide Colombo; Zbigniew Kowalski; Maria Przyłucka; Albin Zdanowski (Pure and Applied Geophysics, 2015)

The DRASTIC-Sg model: an extension to the DRASTIC approach for mapping groundwater vulnerability in aquifers subject to differential land subsidence, with application to Mexico City - Antonio Hernández-Espriú; J. Antonio Reyna-Gutiérrez; Emilio Sánchez-León; Enrique Cabral-Cano; Jaime Carrera-Hernández; Pedro Martínez-Santos; Sergio Macías-Medrano; Giacomo Falorni; Davide Colombo (Hydrogeology Journal, 2014)

Different properties of P2X7 receptor in hippocampal and cortical astrocytes - Fabio Bianco; Alessio Colombo; Laura Saglietti; Davide Lecca; Maria Pia Abbracchio; Michela Matteoli; Claudia Verderio (Purinergic Signalling, 2009)